Analisis Tingkat Kesukaan Konsumen terhadap Minuman Kekinian “Coconut Shake” - Eddy Roesdiono; Anggi Avita Da Tista (Jurnal Syntax Admiration, 2025)
Along with the development of the times, beverage products began to have many variations. Coconut Shake is a trending drink in Singapore made from coconut, milk, and various flavors. The purpose of this organoleptic test research is to find out the level of preference seen from the taste, aroma, and color of Coconut Shake products and to find out the public acceptance of Coconut Shake products. The results of the study showed that 5 respondents liked the contemporary drink "Coconut Shake", 3 respondents quite liked the contemporary drink "Coconut Shake", and 2 respondents did not like the contemporary drink "Coconut Shake". It can be concluded that the contemporary drink "Coconut Shake" can be accepted by some people.